2010
DOI: 10.1016/j.bbrc.2010.08.079
|View full text |Cite
|
Sign up to set email alerts
|

The adipokine leptin increases skeletal muscle mass and significantly alters skeletal muscle miRNA expression profile in aged mice

Abstract: Age-associated loss of muscle mass, or sarcopenia, contributes directly to frailty and an increased risk of falls and fractures among the elderly. Aged mice and elderly adults both show decreased muscle mass as well as relatively low levels of the fat-derived hormone leptin. Here we demonstrate that loss of muscle mass and myofiber size with aging in mice is associated with significant changes in the expression of specific miRNAs. 57 miRNAs were altered with aging in the mice and many of these miRNAs are, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 36 publications
5
104
1
2
Order By: Relevance
“…A total of 57 miRNAs were differentially expressed in aging murine muscle tissue, including miR-221, which has been shown to regulate differentiation of myogenic precursors (Hamrick et al, 2010). Levels of miR-7, miR-468, miR-542 and miR-698 were increased the most substantially, whereas miR-124a, miR-181a, miR-221, miR-382, miR-434 and miR-455 levels were most decreased upon muscle aging (Fig.…”
Section: Skeletal Musclementioning
confidence: 96%
See 2 more Smart Citations
“…A total of 57 miRNAs were differentially expressed in aging murine muscle tissue, including miR-221, which has been shown to regulate differentiation of myogenic precursors (Hamrick et al, 2010). Levels of miR-7, miR-468, miR-542 and miR-698 were increased the most substantially, whereas miR-124a, miR-181a, miR-221, miR-382, miR-434 and miR-455 levels were most decreased upon muscle aging (Fig.…”
Section: Skeletal Musclementioning
confidence: 96%
“…Aging of skeletal muscle has also been associated with changes in miRNA expression levels (Hamrick et al, 2010). A total of 57 miRNAs were differentially expressed in aging murine muscle tissue, including miR-221, which has been shown to regulate differentiation of myogenic precursors (Hamrick et al, 2010).…”
Section: Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Hamrick et al 73 showed that aged mice (24 months), but not 12-month-old mice, responded to injection with recombinant leptin by increasing the size and mass of muscles (including EDL), and induction in muscle of several miRNAs known to be associated with regeneration and repair. While it is tempting to presume that increased muscle in Dmp1-Cre Mbtps1 cKO mice is solely the result of paracrine signaling by leptin (Figure 6), our phenotype is not superimposable since it is evident at 12 months as well as 26 months of age (unpublished result, JP Gorski) and is restricted to SOL (not EDL) muscles.…”
Section: Dec1 and Dec2 Are Subject To Regulation By Circadian Core Prmentioning
confidence: 99%
“…Muscle and fat are both metabolically active, the latter producing TNF-a, IL-6 and adipokines all of which have a direct catabolic effect on the former, and promote insulin resistance. Leptin and low adiponectin concentrations have been found to negatively impact muscle mass and lead to a decline in muscle quality (Hamrick et al 2010). On a biological level, macrophages in adipocytes or in adipose tissue, produce such proinflammatory cytokines (Fantuzzi 2005) which can upregulate the inflammatory response.…”
Section: Sarcopenic Obesity -A Subset Of Sarcopenia and Obesitymentioning
confidence: 99%